Cost of Capital Estimation in Practice: An Explorative Study on Bangladeshi Companies - Yasmin, Shakila; Bashar, Syeda Mahrufa (AIUB Journal of Business and Economics, 2016)
This study investigates cost of capital estimation practices of companies in Bangladesh. CEO/CFO background and company size effect on practices in cost of capital estimation have also been explored. Structured questionnaire survey was conducted on 50 companies from different industries in Bangladesh selected on the basis of access to information. Frequency distribution and cross-tab analysis were done. Results reveal that majority of the companies estimate cost of capital. Unlike past studies where use of CAPM is prevalent, this study reveal historical average return as the most commonly method of estimating cost of equity. Most recent lending rate from banks is the commonly used proxy of cost of debt. Majority companies adjust cost of debt for tax. Use of WACC is prevalent but most companies use book value debt and equity in WACC. Majority companies adjust cost of capital for inflation, exchange rate and interest rate risk whereas only few adjusts for term structure risk and risk of financial distress. CEO/CFO tenure demonstrates strong association with the use of market value debt in WACC.